Diabetes foot screening: Challenges and future strategies. (March 2019) - Formosa, C.; Chockalingam, N.; Gatt, A.
Highlights: A phenomenological study to explore the stakeholder perspectives on diabetic foot screening. Current diabetes foot screening is inadequate and has shortcomings. National cultures and local practices have a detrimental influence on diabetes foot care. Abstract: Background: Healthcare options for people with diabetes is still not uniform both within and between countries. This is particularly evident for diabetic foot disease. The number of existing documents/guidelines, together with discrepancies which exist between different organizations or countries can lead to confusion for both practicing health care professionals and new countries or organizations who are in the process of developing local clinical guidelines. This study was aimed at exploring different stakeholder perspectives with a view to develop and introduce culturally competent foot screening guidelines. Methods: A phenomenological study which incorporated non-structured interviews with eleven local stakeholders and experts related to the field were conducted to explore interviewees' perspectives regarding foot screening guidelines in Malta. Findings: Qualitative analysis identified 3 key themes from the data highlighting barriers to the implementation of diabetes foot screening guidelines. These focused on organizational factors, healthcare professional factors and patient factors. Conclusion: Current procedures related to diabetes foot screening has shortcomings. The findings of this study clearly highlight the need for change in current practices if effective diabetic foot screening is to be offered. Recommendations from this study are relevant to other countries especially those who share same cultures and practices. Making changes today and implementing them in the appropriate manner could make a world of difference in diabetes foot care.